Analisis Framing Zong Dang Pan dan Gerald M. Kosicki pada Pemberitaan Kasus Dugaan Ujaran Kebencian Habib Bahar Bin Smith kepada Presiden Joko Widodo - Setiawan, Hendra; Nulhakim, Lukman (Jurnal Artikula, 2019)
This study discusses the analysis of news framing on Kompas.com online media in reporting cases of alleged hate speech carried out by Habib Bahar bin Smith to President Joko Widodo. The analysis was conducted based on the framing approach of Zong Dan Pan and Gerald M. Kosicki. The research method uses a qualitative descriptive approach that is oriented to content analysis. The results of the study can be concluded that Kompas.com prepares the news of alleged Habib Bahar bin Smith's hate speech to President Joko Widodo using the reverse pyramid technique. In addition, the facts submitted use a reference source from the quotation of the informant's statement. The news presented still carries the concept of 5W + 1H with the main emphasis on the elements of why and what (why and what). Likewise the lead is delivered with the main facts and continued supporting facts in the next paragraph.